The Effectiveness of Podcast on Listening Skill for Vocational School Students - Rizkia Ade Putri Sabrila; Tri Wintolo Apoko (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Podcasts are digital audio files that can be accessed by everyone with an internet connection where the content is ready to be listened to without minding the time and place. Currently, podcasts are listened not only for entertainment but also for educational purposes, one of which is to improve students' listening skills. This research aimed to investigate the effectiveness of using podcasts on students’ listening skills at Vocational High School No. 18, Jakarta. With one group pre-test post-test design, this research utilized the pre-experimental method, which was conducted in three meetings. The samples for this research were 33 students of Accounting Department chosen randomly. To gather the data, the researcher used a listening test with 15 multiple choices and a 10 fill-in-the-blank form as the instrument, both for the pre-test and post-test. IBM SPSS 24 was used to perform quantitative analysis on the data. The result of the data analysis revealed that the students’ mean score in the post-test was higher than in the pre-test (87.03 > 55.15). Thus, it was found that the significant value was 0.000 which was lower than the alpha of 0.05 (0.000 < 0.05). It can be concluded that the Hi is accepted and the Ho is rejected. This study recommends that teachers should consider podcasts in teaching listening skill.